2002
DOI: 10.1097/00003246-200209000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperventilation on cerebral blood flow in traumatic head injury: Clinical relevance and monitoring correlates*

Abstract: Hyperventilation increases the volume of severely hypoperfused tissue within the injured brain, despite improvements in cerebral perfusion pressure and intracranial pressure. Significant hyperperfusion is uncommon, even at a time when conventional clinical management includes a role for modest hyperventilation. These reductions in regional cerebral perfusion are not associated with ischemia, as defined by global monitors of oxygenation, but may represent regions of potentially ischemic brain tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 267 publications
(128 citation statements)
references
References 45 publications
(95 reference statements)
5
120
0
3
Order By: Relevance
“…Most guidelines focus on ICP control as a means to maintain adequate CPP. 34 Current medical treatments to reduce ICP include hyperosmolar therapy (such as mannitol or hypertonic saline), 53 hyperventilation, 15,47 sedation and paralytics, and head of bed elevation. In addition, barbiturate-induced coma 2 and hypothermia 7 have been shown to reduce cerebral metabolic rate and oxygen demands, offering a protective role.…”
Section: Surgical Interventions For Tbi In the Pediatric Populationmentioning
confidence: 99%
“…Most guidelines focus on ICP control as a means to maintain adequate CPP. 34 Current medical treatments to reduce ICP include hyperosmolar therapy (such as mannitol or hypertonic saline), 53 hyperventilation, 15,47 sedation and paralytics, and head of bed elevation. In addition, barbiturate-induced coma 2 and hypothermia 7 have been shown to reduce cerebral metabolic rate and oxygen demands, offering a protective role.…”
Section: Surgical Interventions For Tbi In the Pediatric Populationmentioning
confidence: 99%
“…Adult TBI studies demonstrate that CBF reduction early after injury increases regional cerebral ischemia [68,69]. However, decrease in CBF may not be problematic if, following TBI, baseline CMRO 2 is low and there is a compensatory increase in oxygen extraction fraction [70].…”
Section: Cerebrovascular Physiology After Tbi Altered Cerebral Blood mentioning
confidence: 99%
“…Disturbances in cerebral blood flow (CBF are also a common sequela of head injury and have been documented both experimentally (Yamakami and McIntosh, 1991;Bryan et al, 1995;Kochanek et al, 1995;Forbes et al, 1997;Hendrich et al, 1999;Lythgoe et al, 2003) and clinically (Bouma et al, 1991;Marion et al, 1991;Martin et al, 1997;Coles et al, 2002). CBF abnormalities have been shown to be an important mechanism underlying secondary brain damage experimentally (Jenkins et al, 1989;Giri et al, 2000) and clinically have been shown to be strongly associated with poor outcome (Robertson et al, 1992).…”
mentioning
confidence: 99%